2020
DOI: 10.3390/en13020301
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Mapping of Solar Irradiance for Korea by Using COMS MI Satellite Images and an Artificial Neural Network Model

Abstract: The power capacity of solar photovoltaics (PVs) in Korea has grown dramatically in recent years, and an accurate estimation of solar resources is crucial for the efficient management of these solar PV systems. Since the number of solar irradiance measurement sites is insufficient for Korea, satellite images can be useful sources for estimating solar irradiance over a wide area of Korea. In this study, an artificial neural network (ANN) model was constructed to calculate hourly global horizontal solar irradianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Despite the technological advancements of H8 such as higher spatial resolution, the superior performance of COMS bands can be explained in part by the different orbits of the two satellites. COMS is situated at 128.2 • E and adjusted to the Korean peninsula, whereas H8 is at 140.7 • E, which is biased to the east of Korea [24]. However, some of the differences in p% of NMAE between COMS and H8 were marginal and possibly insufficient to differentiate particularly superior performance of a single satellite dataset.…”
Section: Comparison Between Coms and H8mentioning
confidence: 98%
See 3 more Smart Citations
“…Despite the technological advancements of H8 such as higher spatial resolution, the superior performance of COMS bands can be explained in part by the different orbits of the two satellites. COMS is situated at 128.2 • E and adjusted to the Korean peninsula, whereas H8 is at 140.7 • E, which is biased to the east of Korea [24]. However, some of the differences in p% of NMAE between COMS and H8 were marginal and possibly insufficient to differentiate particularly superior performance of a single satellite dataset.…”
Section: Comparison Between Coms and H8mentioning
confidence: 98%
“…More recent studies have focused on integrating meteorological satellite images in more complex machine learning models and deep learning networks, as past studies have demonstrated that such methods have the potential to yield superior forecast accuracy, particularly for shorter forecast time horizons [8]. COMS images were used to estimate solar radiation using a deep neural network (DNN) [23,24] and Multi-functional Transport Satellite (MTSAT) images were used to estimate hourly global solar radiation [25]. The MTSAT satellite was replaced by H8 in 2015.…”
Section: Pv Forecast Using Satellite Image Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained show very good accuracy. In this regards, it noticed that in many countries, the number of GHI measurement locations is sufficient as in KSA and insufficient in other countries as in Korea [37], [38], where the satellite images can be helpful sources for getting the GHI over a wide area space, in these cases, usually predicted by secondary parameters such as readily obtainable climatic variables.…”
Section: Literature Reviewmentioning
confidence: 99%